Special features of plasma generation and beam formation for fore-vacuum plasma electron sources - Oks, E. M. (IEEE conference record-abstracts - IEEE International Conference on Plasma Science, 2015)
Summary form only given. The paper reviews results of further development and applications of so called fore-vacuum plasma electron sources. The fore-vacuum pressure plasma-cathode electron sources provide efficient generation of continuous and pulsed electron beams in the otherwise inaccessible pressure range from several Pa to about one hundred Pa. Interest in the generation of electron beams at fore-vacuum pressures is dominated by the possibility of their use for surface treatment of dielectric (insulating) materials, ceramics, polymers and some others. This kind of e-beam sources utilizes either a hollow-cathode glow discharge or a cathodic arc discharge for formation of emission plasmas. Arc is mainly used for pulsed mode of electron source operation. Transition of hollow cathode glow to cathodic arc, with its associated cathode spots, follows from the need to increase the electron beam current. The papers presents some of the characteristics and parameters of a pulsed cathodic arc discharge as configured for use in a forevacuum-pressure plasma-cathode electron source for the generation of broad electron beams. Main goal of such research was achievement an uniform distribution of electron beam current density. Another subject to report is demonstration the possibility to obtain homogeneous dense beam plasma in a closed dielectric cavity using a dc forevacuum plasma electron source based on hollow cathode glow. At optimum electron energy and gas pressure, the plasma density distribution lengthwise the cavity is inhomogeneous to no more than 10 %.